Las redes sociales como lugar de construcción de contrapoder - Andrade Medrano, Juan Carlos (2017)
This article presents the analysis about how local and national governments require strategies to legitimate their political power, based on the construction of ideologies. This permits the exercise of governmental authority through an elaborat-ed and convincing speech, allowing the development of public opinion. For the citi-zens, this helps in the understanding and assumption of these politic messages through virtual social networks. Accordingly, it can be said that there is a multimedia, interactive and expres-sive social culture, facing the needs of self-actualization, belonging, construction and deconstruction of identity and power; this reflects the need for spaces of free expres-sion and participation for the citizens, against and in favor of the government. Through social networks, the citizens have the opportunity to create and transmit content in real time, generating strategies of organization to complaint or propose actions, influencing the social, political and cultural spheres. Thus, virtual social networks create counter-speeches for the messages built by the governmental power. Therefore, this article analyses the role of mass communication, studying the influence of the social networks as scenarios of counter-power for the Estate through the managing of messages in different versions, from hypodermic uses to reception exercises studied in the functionalist theory. The evidence has been gath-ered from two virtual platforms which are: Facebook and Twitter, and the official page of the Presidency of Ecuador with the political subject: The Inheritance Law in Ecuador.